ANALISIS PENGARUH INSENTIF PAJAK TERHADAP KINERJA DAN NILAI PERUSAHAAN (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2018-2021) - Raya Rosita Dewi; Abdul Rohman (Diponegoro Journal of Accounting, 2023)
The purpose of this study is to find empirical evidence on whether the tax incentive policy in the form of a reduction in corporate tax rates in response to the Covid-19 pandemic affects firm performance and value and whether firm performance affects firm value. The dependent variables of this study include company performance in the form of return on assets (ROA) and company value in the form of Tobin's Q, while the independent variables include tax incentives as measured by tax planning and company performance in the measure of return on assets (ROA). The research population used is manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2018-2021. The research sample was selected using purposive sampling method so as to get a total of 324 samples from the 4-year research period. The type of data in this study is quantitative data sourced from secondary data. The hypothesis testing method in this study was carried out using the paired sample t-test and multiple regression analysis. The findings of this study indicate that tax incentives have a positive effect on firm performance and firm value. Meanwhile, firm performance has a negative effect on firm value.